Law Enforcement Intelligence as a Preventive Strategy in Eradicating Judicial Mafia in Indonesia - Hartoyo (Faculty of Law, Universitas Pekalongan, 2024)
The practice of judicial mafia is still an acute problem in law enforcement in Indonesia because it weakens the function of the judiciary as a pillar of justice. The supervisory mechanisms that have been applied so far emphasize more on formal and procedural aspects, so they are often ineffective in uncovering judicial mafia networks that operate systematically and covertly. This study aims to examine the use of Law Enforcement Intelligence (LEI) as a more proactive prevention strategy in efforts to combat the judicial mafia. By using normative legal research methods through analysis of laws and regulations and a conceptual approach, this study identifies weaknesses in the judicial oversight system. The results of the study indicate that the integration of law enforcement intelligence can strengthen early detection, enable mapping of patterns of deviation, and provide a strategic information base for judicial institutions. The implementation of LEI demands support for regulatory reform and inter-agency coordination so that the judicial system is more accountable, transparent, and resilient against the practice of legal mafia.